Czy Brexit przyspieszy rewizję traktatu lizbońskiego i uratuje Unię Europejską? - Józef M. Fiszer (Ksiegarnia Akademicka Publishing, 2019)
Does Brexit Previously Revise the Lisbon Treaty and Rescue European Union? There is no doubt that Brexit is an unprecedented event in the history of European integration and in the history of the European Union (EU). It will certainly be a turning point not only in the history of the EU, but also in Europe, and will have an impact on their place and role in the new, emerging international order. Today it is very difficult to present an accurate diagnosis, and even more, difficult to predict the future of the EU, Europe, and the whole world after Brexit. The purpose of this article is an attempt to answer a few questions, especially on the question contained in its title and to present the opportunities and threat for the European Union after Brexit. In addition, the author is trying to answer the question whether, at all, today, nine years after the entry into force of the Treaty of Lisbon, its revision is needed? Does the EU really need a new treaty? Currently, opinions on this subject are divided among researchers and experts. Many also are afraid that Brexit will be the beginning of the end of the Union, that it will lead to the so‑called diversified integration and then to its disintegration. Others believe that the Brexit may become an accelerator of the European Union’s modernization process, which will, however, require the adoption of a new revision treaty.